How effectively GO-GIS (Google Site Web-Based Multimedia Integrated with Geographic Information System) can increase student’s critical thinking skill in school - Yudistira, Yusuf; Mukminan, Mukminan; Nursa'ban, Muhammad (Pelopor Publikasi Akademika, 2023)
This study aims to develop GO-GIS multimedia and determine the effectiveness of GO-GIS to improve students' critical thinking skills in disaster mitigation and adaptation materials. This research refers to the ADDIE development model which consists of analysis, design, development, implementation, and revision. The product feasibility test was assessed by 1 media validator, 1 material validator and student responses. The results showed that (1) GO-GIS learning media was feasible to use, the results of the feasibility assessment by material experts obtained a score of 4.73, the feasibility assessment by media experts obtained a score of 4.82, the user's response in small group trials obtained an average 4.45. Score indicates very decent. (2) GO-GIS multimedia proved to be effective as a learning medium and there was an increase in students' critical thinking skills in the experimental class (GT = 0.50, N = 35) in the medium category when compared to the control class (GT = 0.23, N = 35) in the moderate category (GT = 0.23, N = 35) in the low. The results of the independent t-test show the sig. 0.03 (sig value < 0.05) and it can be concluded that there is a significant increase in students' critical thinking skills in disaster mitigation between the Experiment class (mean 78.57) and the control class (mean = 71.88).